2014
DOI: 10.1007/s13668-014-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Dairy and Cardiovascular Disease: A Review of Recent Observational Research

Abstract: The consumption of dairy, including milk, cheese and yogurt, has been associated with better quality of diet and reduced risk of cardiovascular disease, the leading cause of death globally. The purpose of this review is to examine recent literature on the relationship between dairy consumption and risk of cardiovascular disease incidence and mortality. Eighteen observational studies were reviewed, the results of which indicate that total dairy intake does not contribute to cardiovascular disease incidence or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Dairy products and a high intake of SF have been linked to an increased risk of CVD [52]. However, recent findings have indicated that the link between CVD and SF may be less straightforward than originally thought [27]; although studies on the relationship between total dairy consumption and CVD risk markers have reported inconsistent results, the review of the literature could point to a potentital protective effect of full-fat milk, cheese, and yogurt, while the data pertaining to dairy fat are inconclusive [53]. Thus, there is a need for research on the effect of individual dairy foods on CVD risk [27,53,54] as well as on the differential effects of the fermented dairy products and the milk from which they are obtained, since there can be variations in their nutrient content [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dairy products and a high intake of SF have been linked to an increased risk of CVD [52]. However, recent findings have indicated that the link between CVD and SF may be less straightforward than originally thought [27]; although studies on the relationship between total dairy consumption and CVD risk markers have reported inconsistent results, the review of the literature could point to a potentital protective effect of full-fat milk, cheese, and yogurt, while the data pertaining to dairy fat are inconclusive [53]. Thus, there is a need for research on the effect of individual dairy foods on CVD risk [27,53,54] as well as on the differential effects of the fermented dairy products and the milk from which they are obtained, since there can be variations in their nutrient content [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings have indicated that the link between CVD and SF may be less straightforward than originally thought [27]; although studies on the relationship between total dairy consumption and CVD risk markers have reported inconsistent results, the review of the literature could point to a potentital protective effect of full-fat milk, cheese, and yogurt, while the data pertaining to dairy fat are inconclusive [53]. Thus, there is a need for research on the effect of individual dairy foods on CVD risk [27,53,54] as well as on the differential effects of the fermented dairy products and the milk from which they are obtained, since there can be variations in their nutrient content [55,56]. Therefore, we focused on the effect of yogurt fermented with conventional startes cultures ( L. bulgaricus , S. thermophilus ) produced from cow’s milk (the most commonly consumed), for which there is little evidence indicating that it lowers serum lipids [27], and of yogurts prepared using ewe’s milk because of their different nutrient content and lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between dairy intake and different disease outcomes have been evaluated in several studies, but reported associations remain contradictory (2)(3)(4)(5)(6)(7)(8)(9)(10). The inconclusive evidence regarding the association between nonfermented milk, specifically, and mortality has been highlighted in a recent systematic review and meta-analysis by Larsson et al (3).…”
Section: Introductionmentioning
confidence: 99%
“…Complex milk fatty acid chemistry and several minerals, such as calcium, magnesium, phosphorus, and potassium provided in relevant concentrations, have been proposed to be involved in the complex mechanism of dairy products and their support to reduce CVD risk [68]. Among the high number of different fatty acids in dairy products, trans-palmitoleic acid, stearic acid, lauric acid, myristic acid, and oleic acid have been associated with beneficial effects on blood lipids and serum lipoprotein levels [56].…”
Section: Cardiovascular Health Menaquinones and Fermented Dairy Promentioning
confidence: 99%